2014
DOI: 10.4103/0259-1162.143153
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of transversus abdominis plane block in patients undergoing emergency laparotomies

Abstract: Background:Pain experienced following laparotomy is largely due to abdominal wall incision. Effective mitigation of this pain is vital to improve patient satisfaction and for early ambulation. We evaluated the efficacy of transversus abdominis plane (TAP) block for postoperative analgesia, as a component of multimodal analgesia.Materials and Methods:Sixty adult ASA physical status I to III patients undergoing emergency laparotomy under general anesthesia were recruited for this double-blind, randomized, contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…48,49 A small RCT in emergency laparotomy found that transversus abdominus plane blocks lowered pain scores and postoperative need for rescue analgesia compared with placebo. 50 Findings are consistent with earlier MAs, which demonstrated benefits from truncal nerve blocks in open and laparoscopic elective abdominal operations. 51,52 Summary and recommendations Epidural analgesia and truncal regional blocks are potentially beneficial for emergency major abdominal operations and should be considered in the appropriate clinical setting.…”
Section: Evidencesupporting
confidence: 85%
“…48,49 A small RCT in emergency laparotomy found that transversus abdominus plane blocks lowered pain scores and postoperative need for rescue analgesia compared with placebo. 50 Findings are consistent with earlier MAs, which demonstrated benefits from truncal nerve blocks in open and laparoscopic elective abdominal operations. 51,52 Summary and recommendations Epidural analgesia and truncal regional blocks are potentially beneficial for emergency major abdominal operations and should be considered in the appropriate clinical setting.…”
Section: Evidencesupporting
confidence: 85%
“…They stated that open TAP blocks are safe and reduce postoperative opioid requirements and sedation after liver resection and other surgeries as hemi-colectomies, liver transplant, and emergency laparotomy, respectively. [212223]…”
Section: Discussionmentioning
confidence: 99%
“…It is still controversial about whether QL block can be safely performed in the case of coagulopathy or in the anti-coagulated patient [ 33 ]. Some practitioners suggest that plane blocks may be safe with changes in coagulation function [ 34 ]. As warned by the latest evidence-based guidelines for regional anesthesia use in patients receiving antithrombotic or thrombolytic therapy released by the American Society of Regional Anesthesia and Pain Medicine, deep regional anesthesia performed in the anti-coagulant patient may result in significant morbidity that has already been reported in multiple case reports [ 35 ].…”
Section: Discussionmentioning
confidence: 99%